Impression management strategies in the chairmen’s statements: evidence from the Portuguese banking industry - Oliveira, J. S.; Azevedo, G. M. C.; Pinheiro, S. F.; Borges, M. F. R. (International financial reporting standards and new directions in earnings management, 2019)
This chapter assesses the influence of organizational performance in the adoption of impression management strategies in the Chairmen's statements of the Portuguese financial companies. It also evaluates the impact of the financial crisis on the adoption of impression management strategies. To this end, and using the content analysis of the Chairmen's statements included in the individual annual reports for 2006-2012 of 27 financial institutions, the authors conclude that even throughout the financial crisis period, Portuguese financial companies did not tend to adopt more impression management strategies. However, they have seen that in some years there is some evidence of its adoption.